ОПРЕДЕЛИТЬ БОЛЕЗНЬ ФАБРИ - Г. П. Арутюнов; Н. А. Былова (Архивъ внутренней медицины, 2013)
This article is an analysis of the clinical case of differential diagnosis of Fabry disease. Pecular symptoms and the principles of diagnosis of Fabry disease, as well as current treatment options for this disease are presented.